Identifikasi Bahaya, Penilaian Risiko dan Upaya Pengendalian: Studi Kasus di PT. Metta Santoso Joyo - Harley Putra Njoto; Kriswanto Widiawan (Jurnal Titra, 2023)
PT. Metta Santoso Joyo is a company that was established in 2002 and engaged in the plastics industry which produces various kinds of plastic pellets. During 21 years, there have been various occupational accidents and diseases. The purpose of this final project is to identify potential hazards, provide risk assessments, and provide risk control recommendations to the company. Research only done at the raw material washing area and plastic pellet production area, because these two areas where accidents and diseases occur most often. Proposed risk controls are given only to potential hazards that have high and extreme risk rating. In the raw material washing area, there are 4 potential hazards with high risk rating and 1 potential hazard with extreme risk rating. In the plastic pellet production area, there are 5 potential hazards with high risk rating, and 2 potential hazards with extreme risk rating. Proposed risk controls include 5 design techniques, 6 administrative controls, and 5 use of personal protective equipment. If the proposed risk control implemented, it’s predicted the potential hazard that have high and extreme risk rating will change to 10 moderate risk rating and 2 low risk rating.